(untitled) (Colombia Medica, 2017)
Introduction: Initial treatment of the HIV is based on the use of three drugs, two of which are nucleoside analog reverse-transcriptase inhibitors. There are three combinations of these drugs which have been approved by different guidelines, each with divergent results in terms of efficacy and safety.Objective: To compare the efficacy and safety of these three combinations.Methods: Systematic review and network meta-analysis of randomized clinical trials comparing fixed doses of Tenofovir Disoproxil Fumarate / Emtricitabine (TDF/FTC), Abacavir / Lamivudine (ABC/3TC) and Zidovudine / Lamivudine (ZDV/3TC).Results: Seven clinical trials met the eligibility criteria. The results suggested higher efficacy with TDF/FTC vs. ABC/3TC at 96 weeks and vs. ZDV/3TC at 48 weeks. However, there is clinical and statistical heterogeneity. Subgroup analysis were performed by third drug and by level of viral load prior to treatment, and found no differences in virological control. Network meta-analysis could only be carried out with TDF/FTC vs. ZDV/3TC, and the proportion of patients with virological response, with no differences at 48 weeks nor at 96 weeks. Direct comparisons showed an increased risk of bone marrow suppression of ZDV/3TC vs. TDF/FTC and of ABC/3TC hypersensitivity reactions vs. ZDV/3TCConclusions: The results did not show differences in effectiveness among the interventions. However, due to the heterogeneity of the third drug and the follow-up time between the included studies, this result is not definitive. The results raise the need for further studies to help improve treatment recommendations in patients infected with HIV.